Mathematical Modeling and Performance Evaluation of 3D Ferroelectric Negative Capacitance FinFET - Alam, Sayem Ul; Uddin, Rukon; Alam, Md. Jahangir; Raihan, Ahamed; Mahtab, Sheikh S.; Bhowmik, Subrata (Modelling and Simulation in Engineering, 2022)
Ferroelectric negative capacitance materials have now been proposed for lowering electronics energy dissipation beyond basic limitations. In this paper, we presented the analysis on the performance of negative capacitance (NC) FinFET in comparison with conventional gate dielectrics by using a separation of variables approach, which is an optimal quasi-3D mathematical model. The result has been signified steeper surface potential (ψ), lower threshold voltage (Vth), 1.2 mA of on-state current (Ion), and enhanced immunity of negative capacitance FinFET against short channel effects (SCE’s) like 35.3 mV/V of drain-induced barrier lowering (DIBL), 60 mV/dec of subthreshold swing (SS) along with smallest off state current (Ioff) among another conventional gate dielectric. Hence, NC FinFET can be a potential candidate for low power and high-performance device.